Help-seeking behaviors for female sexual dysfunction: a cross sectional study from Iran - Montazeri Ali; Vahdaninia Mariam; Goshtasebi Azita (BMC, 2009)
Abstract Background Female sexual dysfunctions (FSD) are prevalent multifactor problems that in general remain misdiagnosed in primary health care. This population-based study investigated help-seeking behaviors among women with FSD in Iran. Methods This was a cross sectional study carried out in Kohgilouyeh-Boyer-Ahmad province in Iran. Using quota sampling all sexually active women aged 15 and over registered in primary health care delivery centers were studied. Experience of sexual problems was assessed using an ad-hoc questionnaire (Female sexual dysfunction: help-seeking behaviors survey) containing 14 items. Trained female nurses interviewed all participants after a verbal informed consent. Data were analyzed in a descriptive manner. Results In all 1540 women were studied. Of these, 786 (51%) cases had experienced at least one of the FSD problems. Results showed that 35.8% of women with FSD had sought no professional help and the most reasons for not seeking help were identified as: 'time constraints' and believing that it 'did not occur to me' (39.1 and 28.5% respectively). Sixty one percent of women who sought help for FSD reported that 'doctor gave me a definite diagnosis' and 'a definite treatment plan was given' in 57% of cases. Conclusion The study findings indicated that FSD problems were prevalent and many women did not seek help for their problem. Finding 'time constraints' and believing that the problem 'did not occur to me' as the most cited reasons for not seeking help might facilitate to understand potential barriers that exist in recognition and treatment of the female sexual dysfunctions. Since FSD might have a negative impact on interpersonal relationships and women's quality of life, it seems that there is need to address the problem both at local and national primary health care services.